Effect of Fetal Bovine Serum Concentration on Detection and Morphological Identification of Blastocystis hominis in vitro - Janendra, Putu Sathiya Adi; Sukarma, Kadek Edy; Sarita, Kadek intan Arta; Maheswari, Kadek Indira; Giri, Made Kurnia Widiastuti; Permasutha, Made Bayu; Pasala, Metamalik (Indonesian Journal of Tropical and Infectious Disease, 2025)
Diarrhea significantly contributes to the high rates of illness and death among young children. Diarrhea can be caused by bacterial infections, viruses, or even parasites. Blastocystis hominis causes parasitic diarrhea, which can be identified by microscopy, culture, and molecular methods. Previous reports have modified the Jones’ culture medium using three different serums, such as human plasma, donkey serum, and horse serum (in Jones’ medium). This research replaces horse serum with fetal bovine serum for detection tests, morphological observation, and diagnosis of B. hominis. The research encompasses five experimental groups, each subjected to varying concentrations of fetal bovine serum: 2%, 10%, 20%, 30%, and 40%. Detection analysis is conducted using the Mc-Nemar test, while the Wilcoxon test is applied to evaluate ordinal data from morphological assessments. Diagnostic tests and metrics such as accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) are performed using MedCalc® software. The findings demonstrate that serum concentrations of 2%, 10%, 20%, and 30% produced effective results in detection tests, morphological identification, and diagnostic evaluations of B. hominis, exhibiting high sensitivity, specificity, PPV, NPV, and accuracy. Fetal bovine serum can be used at a concentration of 2% in a Jones’ medium that has been modified. This depends on the results of detection tests, morphology, and diagnosis.